2008
DOI: 10.1111/j.1538-7836.2008.03104.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphate as a general procoagulant agent

Abstract: Summary. Background: Polyphosphate is secreted by activated platelets and we recently showed that it accelerates blood clotting, chiefly by triggering the contact pathway and promoting factor (F) V activation. Results: We now report that polyphosphate significantly shortened the clotting time of plasmas from patients with hemophilia A and B and that its procoagulant effect was additive to that of recombinant FVIIa. Polyphosphate also significantly shortened the clotting time of normal plasmas containing a vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 31 publications
1
70
1
1
Order By: Relevance
“…23 PolyP can also shorten the clotting times of plasma from patients with hemophilia A or B, or patients taking vitamin K antagonists. 23 It is thus tempting to speculate that polyP of the size secreted by human platelets (or suitable polyP derivatives) might be useful as injectable hemostatic agents. Long-chain polyP may have utility as a topical hemostatic agent, and indeed, adding polyP to chitosan-based wound dressings made them substantially more procoagulant.…”
Section: Conclusion and Some Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 PolyP can also shorten the clotting times of plasma from patients with hemophilia A or B, or patients taking vitamin K antagonists. 23 It is thus tempting to speculate that polyP of the size secreted by human platelets (or suitable polyP derivatives) might be useful as injectable hemostatic agents. Long-chain polyP may have utility as a topical hemostatic agent, and indeed, adding polyP to chitosan-based wound dressings made them substantially more procoagulant.…”
Section: Conclusion and Some Future Directionsmentioning
confidence: 99%
“…Studies from our laboratory and others have shown that polyP acts at the beginning, middle, and end of the blood clotting cascade (Figure 2), with prohemostatic, prothrombotic, and proinflammatory effects. 5,[23][24][25][26][27][28][29][30] …”
mentioning
confidence: 99%
“…9 Subsequent studies confirmed that polyP is prothrombotic and proinflammatory in in vivo mouse models 8,10 and that there are multiple steps in the coagulation cascade at which polyP acts to achieve this end. 8,[11][12][13][14][15][16][17] The effects of polyP on coagulation are concentrationand size-dependent. 14 Thus, platelet-sized polyP (P 60-100 ) primarily accelerates thrombin-mediated activation of factor XI and factor V, whereas larger-size polyP triggers coagulation via contact activation of factor XII and enhances fibrin polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…1 Previously, PolyP has been shown to influence blood coagulation by (1) induction of factor XII activation (contact activation), (2) acceleration of factor V activation by factor Xa, and (3) enhancing fibrin fibril thickness. 1,6,7 PolyP is a linear polymer of inorganic phosphate groups linked by high-energy phosphoanhydride bonds. A minimum PolyP chain length is required to support factor XI activation by thrombin, suggesting a template mechanism in which factor XI and thrombin bind to the polymer in proximity to each other.…”
Section: David Gailani Vanderbilt Universitymentioning
confidence: 99%